2021
DOI: 10.4103/ija.ija_57_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hypotensive properties of dexmedetomidine versus clonidine for induced hypotension during functional endoscopic sinus surgery

Abstract: Background and Aims: Excessive bleeding is a major concern in functional endoscopic sinus surgery (FESS) under general anaesthesia; this can be decreased by various hypotensive agents. This study was conducted to compare the hypotensive effectiveness and haemodynamic stability of dexmedetomidine and clonidine in patients undergoing elective FESS. Methods: In this prospective double-blinded interventional study, 70 adult patients of either sex, 20–50 years of age, posted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Controlled hypotension plays a crucial role in FESS by effectively reducing intraoperative enhancing visibility quality and bleeding of the surgical site [9] . In accordance with our findings, Rokhtabnak et al [10] concurred on the topic of bleeding, surgeon satisfaction and visibility in the field of surgical.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled hypotension plays a crucial role in FESS by effectively reducing intraoperative enhancing visibility quality and bleeding of the surgical site [9] . In accordance with our findings, Rokhtabnak et al [10] concurred on the topic of bleeding, surgeon satisfaction and visibility in the field of surgical.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects of DEX made it a desirable option for establishing hypotensive anesthesia during FESS (10)(11)(12). However, most studies that used DEX during FESS reported delayed emergence from anesthesia and higher postoperative sedation with or without delay in a postanesthesia care unit (PACU) discharge time (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled hypotension could precipitate serious perioperative consequences, including acute kidney injury [AKI], hypoperfusion or ischemia to other vital organs, and acidosis [4] . That's why identification of the risk factors for that problem is crucial for its prevention [5] .…”
mentioning
confidence: 99%